Value, Transvaluation and Globalization - Steffen Dalsgaard; Ton Otto (eTropic: electronic journal of studies in the tropics, 2014)
Value has been a central concept in anthropology and sociology since the birth of these disciplines (e.g. Marx, Simmel, Weber). In recent decades the concept has seen a revival (e.g. Graeber 2001; Eiss and Pedersen 2002; Pedersen 2008; Otto and Willerslev 2013), but while it has been debated and discussed, assessed and evaluated extensively, there are nonetheless still many things to be said about it. This volume addresses a particular perspective on value through the lens of ‘transvaluation’, and how transvaluation may denote a process that occurs in our current world system as an intrinsic effect of contemporary globalization.